Adherence to the 2009 Consensus Guidelines for Vancomycin Dosing and Monitoring Practices: A Cross‐Sectional Survey of U.S. Hospitals. Issue 12 (29th July 2013) - Davis, Susan L.; Scheetz, Marc H.; Bosso, John A.; Goff, Debra A.; Rybak, Michael J.
<x xml:space="preserve">Abstract</x> Study Objectives To describe the implementation of vancomycin dosing and monitoring practices recommended by the consensus guidelines in a diverse sample of hospitals, and to identify needs for quality improvement and research. Design Cross‐sectional study using an online survey instrument. Setting Making a Difference in Infectious Diseases Pharmacotherapy (MAD‐ID) Research Network. Participants A total of 163 respondents from MAD‐ID who work in antimicrobial stewardship and represent unique hospitals. Measurements and Main Results The survey population represented a wide range of patient populations (96% adult, 49% pediatric, and 23% long‐term care) and settings (52% not‐for‐profit nonuniversity, 31% university based, and 11% for profit). Automatic consultation of pharmacy services for all vancomycin dosing was reported in 51% of the institutions. Among the dosing and monitoring practices endorsed by the consensus guidelines, participant institutions commonly followed these recommendations: use of trough concentrations without peak concentrations, maintenance of trough concentration higher than 10 mg/L, and target trough concentrations of 15–20 mg/L for complicated infections. In contrast, there was less consistent application of appropriate timing of trough concentrations, use of loading doses, and use of actual body weight. The remaining challenges and controversies surrounding vancomycin dosing are discussed. Conclusion Despite the availability of consensus guideline recommendations, practices for dosing and monitoring of vancomycin are not universally applied. The findings of this survey highlight many opportunities for future research and quality improvement strategies.